Experimental Transmission of Spike Disease of Sandal, Santalum album by the Leaf-hopper, Nephotettix virescens (Distant) (Homoptera : Cicadellidae) - Sivaramakrishnan, V. R.; Sen-sarma, P. K. (Indian Forester, 1978)
During the current entomolgical investigations on the spike disease of sandal, Nephotettix Virescens (Distant) was incriminated as an insect vector transmitting the spike disease of sandal in nature in some of the areas. Earlier two species of leaf-hoppers namely Coelidin indica Walker (=Jassus indicus Walker) and Moonia albimaculata Walker (Homoptera : Cicadellidae) were reported to have been incriminated as insect vectors of spike disease of sandal. Experimental transmission of spike disease of sandal through the insect vector, Nephotettix Virescens Distant (Homoptera : Cicadellidae) commonly known as "Rice Green leaf-hopper" is presented in this paper. At least sixty leaf-hoppers were required for disease transmission in the transmission cages. The insect transmission of disease was confirmed by biometrical ratios, stain test and retransmission by grafting.